2010
DOI: 10.1051/0004-6361/200913215
|View full text |Cite
|
Sign up to set email alerts
|

Three intermediate-mass young stellar objects with different properties emerging from the same natal cloud in IRAS 00117+6412

Abstract: Aims. Our main aim is to study the influence of the initial conditions of a cloud in the intermediate/high-mass star formation process. Methods. We observed with the VLA, PdBI, and SMA the centimeter and millimeter continuum, N 2 H + (1-0), and CO (2-1) emission associated with a dusty cloud harboring a nascent cluster with intermediate-mass protostars.Results. At centimeter wavelengths we found a strong source, tracing a UCH ii region, at the eastern edge of the dusty cloud, with a shell-like structure, and w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…the higher sensitivity of the PdBI is not the reason we do not detect the 1.3 mm counterparts of these cores. Following the method described in the appendix of Palau et al (2010), we estimated that the largest structure from the shortest baselines of our observations that our PdBI observations could recover is ∼9.5 , while for the SMA observation it is ∼5.7 . Thus the relatively smooth distributed MM2, MM4, and MM6 were filtered out by the SMA observations.…”
Section: Millimeter Continuum Emissionmentioning
confidence: 99%
“…the higher sensitivity of the PdBI is not the reason we do not detect the 1.3 mm counterparts of these cores. Following the method described in the appendix of Palau et al (2010), we estimated that the largest structure from the shortest baselines of our observations that our PdBI observations could recover is ∼9.5 , while for the SMA observation it is ∼5.7 . Thus the relatively smooth distributed MM2, MM4, and MM6 were filtered out by the SMA observations.…”
Section: Millimeter Continuum Emissionmentioning
confidence: 99%
“… c Largest angular scale (at half power) detectable by the interferometer, estimated from the minimum baseline of the array configuration, and following the appendix in Palau et al (2010). For the lines observed in C‐ and D‐configuration, this refers to the merged uv coverage. …”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…For example, Palau et al (2007) found a cluster of young stellar objects in the ultra-compact H ii region IRAS 20293+3952 with a similar range of infrared-millimeter colors as found here. Although we do not discuss spectral line observations here, these provide many additional ways to delineate evolutionary stages, through signatures of masers, hot and cold core chemistry, core collapse, and protostellar outflows (Beuther et al 2007;Fontani et al 2009;Brogan et al 2009Brogan et al , 2011Palau et al 2010;Wang et al 2011).…”
Section: Discussionmentioning
confidence: 99%